Characterization of biomedical Ti-16Nb-(0-4)Sn alloys produced by Powder Injection Molding - GÜLSOY, HAMİT ÖZKAN (PERGAMON-ELSEVIER SCIENCE LTD, 2017)
Ti alloys are the most remarkable group of biomedical implant materials because of their properties such as low elastic modulus, low density, super bio-compatibility, high strength/density ratio. Metastable beta-Ti alloys have lower elastic modulus compared to other types so it is possible to reduce the biomechanical mismatch and stress shielding effect of the implant-bone interfaces. Powder Injection Molding process (PIM), is an alternative method of implant production, offers some advantages such as low cost, net shape production, precise tolerances and possibility to produce complex parts simply. In this study, Ti-16Nb-XSn (X:0,2,4 wt%) alloys were produced through PIM method. It is observed that Sn addition has negative effect on the sintered density of the alloy when sintering process conducted at lower temperatures (1250-1400 degrees C) but it has no or minimum effect when sintering temperature increased to 1550 degrees C (96% TD). Microstructure of the emerging alloys was comprised of alpha + beta phases, hardness of the alloys was between 4500 and 8000 MPa. Also results showed that Elastic Modulus of the Ti-16Nb alloy decreased to 77 GPa from 128 GPa by adding 2% Sn to the base alloy but it observed that no further decreasing possible by increasing amount of the Sn. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: LOW YOUNGS MODULUS; MECHANICAL-PROPERTIES; SHAPE-MEMORY; SN ADDITION; BETA-TI; NB; MICROSTRUCTURE; BEHAVIOR; PHASE; SUPERELASTICITY